DESIGN OF AN ELECTROSTATIC IMMERSION LENS USING THECHARGE DENSITY METHOD - Ahmad, Ahmad K; Ajeel, Khalil K; Hamad, Bassma H (Al-Nahrain Journal of Science, 2010)
A computational investigation has been carried out in the field of non-relativistic chargedparticle optics using the charge density method as a boundary value problem with the aid of a personal computer under the absence of space-charge effects. This work has been concentrated on designing a two-electrode electrostatic immersion lens whose electrodes are cylindrical in shape separated by an air gap. The variable parameters of the two electrodes are the applied voltage ratio and the radii of the two cylindrical electrodes. The axial potential distribution of an electrostatic immersion lens has been computed by taking into consideration the distribution of the charge density due to the voltages applied on the two cylindrical electrodes. Potentials have been determined anywhere in space by using Coulomb s law. The optical properties of the immersion lens have been investigated under finite and zero magnification conditions.